Professional Doctorates: International Experience and Russian Context - B. I. Bednyi; S. K. Bekova; N. V. Rybakov; E. A. Terentev; N. A. Khodeeva (Высшее образование в России)
The diversification of forms and types of doctoral programs is currently a global trend. Universities across the globe offer programs that differ in the modes of training, characteristics of the target audience, and possible labor markets after graduation. In Russia, doctoral education exists in a unified format, focusing primarily on the academic labor market. Recently, there have been discussions about the need to expand the range of programs and the types of academic degrees in Russia. In this article, we present the analysis of professional doctoral programs: in response to what challenges and needs they appeared, how they are implemented, in what forms they exist. In addition, we consider the Russian experience of implementing professional doctoral programs; analyze the existing opportunities and barriers for their development. Based on the analysis, we came to a conclusion about the relevance of the professional doctoral programs’ development in Russia, the expediency of simplifying the conditions for their implementation and legitimizing special requirements for the design of dissertations with an applied orientation.